Synthesis of Two Monomeric Tri‐Substituted γ*‐Dawson‐Type Polyoxotungstates. Issue 8 (12th February 2020) - Li, Ning; Zhang, Sufang; Zhao, Jianguo; Pan, Qiliang; Xing, Baoyan; Li, Jingwei; Jiang, Shang; Qu, Wenshan
Abstract : Two novel tri‐substituted γ*‐Dawson‐type polyoxotungstates H12 [P2 W15 O59 Co(H2 O)3 ]· 15H2 O (1 ) and H12 [P2 W15 O59 Ni(H2 O)3 ]· 15H2 O (2 ) have been successfully synthesized under conventional solution conditions, and characterized in the solid state by powder and single‐crystal X‐ray diffraction, IR spectroscopy, thermogravimetric analysis, and elemental analysis. Structural analysis indicates that they are the tri‐substituted γ*‐Dawson isomers, which are very rare in Dawson‐type polyoxometalates. The magnetic properties of both compounds were studied. In addition, the electrochemical properties of both compounds have also been investigated in H2 SO4 aqueous solution. Abstract : Two tri‐substituted γ*‐Dawson‐type polyoxotungstates have been successfully prepared, which represent the first γ*‐type phosphotungstates, and also the first γ*‐type transition‐metal‐substituted POMs. Their magnetic behavior demonstrates antiferromagnetic interactions within the M 2+ centers (M = Co, Ni). Their electrochemical properties have also been investigated.